FLORISTIC DIVERSITY OF FAMILY ASTERACEAE IN SOUTHERN HARYANA: DISTRICT CHARKHI DADRI - Mohal Lal and Hemant Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The present work is an attempt to document the floristic diversity of family Asteraceae present in district Charkhi Dadri, Haryana (India). The expedition was carried out in various seasons from 2016 to 2019. The study revealed that the family represented by 33 species in over 23 genera. The genera Blumea, Sonchus and Gnaphalium (each representing three species) are dominant in the region followed by Ageratum, Bidens, Eregiron and Launaea (representing two species each). Mostly the members were wild, some of them weeds in cultivated field while genera Blainvillea was found on traces of hill- only. The family represented only herbaceous and shrubby life-forms and no tree were found during expedition.